Erratum: Bragg Reflection and Conversion Between Helical Bloch Modes in Chiral Three-Core Photonic Crystal Fiber (Journal of Lightwave Technology (2020) 38:15 (4100-4107) DOI: 10.1109/JLT.2020.2984464) - Loranger, Sebastien; Chen, Yang; Roth, Paul; Frosz, Michael H.; Wong, Gordon K.L.; Russell, Philip St J. (Journal of Lightwave Technology, 2022)
SUBSEQUENT analysis has revealed that the dispersion relation in (3) in this paper [1] is incorrect, because it does not take proper account of the transformation from the helicoidal to the cartesian frame. The correct analysis has been reported in detail in a recent paper [2]. As a result (3) should be replaced with: (Farmula Presenred) s the topological charge (named orbital angular momentum in the original paper). The term containing α3 yields a very small circular birefringence, which can be neglected. The revised version of Fig. 2 is shown below.
CRIS-Team Scopus Importer:2024-12-16